A Digital Technique to Replicate Edentulous Arches with Functional Borders and Accurate Maxillomandibular Relationship for Digital Complete Denture. Issue 4 (4th March 2020) - Mai, Hang‐Nga; Lee, Du‐Hyeong
Abstract: Correct functional border impression and jaw registration is a challenge when edentulous arches are directly digitized with an intraoral scanner. This article describes a digital workflow to replicate complete edentulous arches with full functional contour, and position them in the centric relation using an intraoral scanner, existing denture, and three‐dimensional image reversal technique. Based on the reconstructed images, the base and dental parts of the new denture can be designed efficiently and predictably.